Simulation and Sensitivity Analysis for H2 Production Using Steam Oxygen Gasification in Aspen Plus - Latif, A.; Ramzan, N. (The Nucleus, 2016)
In this study, steady state simulation model of steam oxygen gasification has been developed in Aspen Plus for hydrogen production using Pakistani Thar coal. Aspen Plus is selected as a simulation tool due to its higher capability of handling solid feed using physical models. Steam oxygen gasifier has been modeled in two steps; first utilizing DECOMP succeeding RGibbs unit operation model. Simulation results include; sensitivity analysis of coal slurry concentration , oxygen to coal mass ratio and gasifier operating temperature. Influence of the above mentioned parameters are analyzed on lower heating value of syngas, thermal efficiency, gasifier efficiency and molar fraction of hydrogen in enriched syngas.Simulation results provide the following optimal operating conditions; 50% solid concentration, 0.48 O2 to coal mass ratio, low shift reactor operating temperature 473 K, high shift reactor operating temperature 623 K and gasifier operating temperature 1173 K for the production of syngas having 92% H2 molar composition.